New age of sustainable capitalism : the business models to drive growth and social change collection - Hart, Stuart L.; Prahalad, C. K. (FTPress Delivers, 2013)
A brand new collection of cutting-edge guides to sustainable capitalism Translate sustainability and "base of the pyramid" strategies into real profits It's time for capitalism's next reinvention. In the new Third Edition of his best-selling Capitalism at the Crossroads, Third Edition , Stuart L. Hart reveals tomorrow's capitalism. He presents new case studies and practical strategies for building companies that are more sustainable, build deeper roots in their markets, play a central role in solving social and environmental problems - and are far more profitable. Hart helps you identify sustainable products and technologies that will drive urgently needed growth and help solve social and environmental problems at the same time. Drawing on his experience consulting with top companies and NGOs worldwide, he shows how to craft your optimal sustainability strategy, and overcome the pitfalls of traditional 'greening' approaches. This edition presents new and updated case studies from the US and beyond, demonstrating what's working and what isn't. It also guides business leaders in building an "infrastructure for sustainability" - one that can survive budgeting and boardrooms, recharging innovation and growth throughout your enterprise. Next, in the 5th Anniversary Edition of his classic The Fortune at the Bottom of the Pyramid , C.K. Prahalad reveals all that's been learned about competing and profiting "at the bottom of the pyramid." Prahalad outlines the latest strategies and tactics that companies are utilizing to succeed in the developing world. He interviews innovative CEOs to discuss what they've learned from their own initiatives, including the Unilever business leader who's built a billion-dollar business in India. You'll find a new case study on Jaipur Rugs' innovative new global supply chain; updates to earlier editions' key cases; and up-to-the-minute information on key industries such as wireless, agribusiness, healthcare, consumer goods, and finance. Prahalad also offers an up-to-date assessment of the key questions his ideas raised: Is there truly a market? Is there scale? Is there profit? Is there innovation? Is this a global opportunity? Five years ago, executives could hope the answers to these questions would be positive. Now, as Prahalad demonstrates, they can be certain of it. From the world-renowned experts in sustainable capitalism Stuart L. Hart and C.K. Prahalad.